Tandem quadruplication of HMA4 in the zinc (Zn) and cadmium (Cd) hyperaccumulator Noccaea caerulescens. - Seosamh Ó Lochlainn; Helen C Bowen; Rupert G Fray; John P Hammond; Graham J King; Philip J White; Neil S Graham; Martin R Broadley (PLoS ONE, 2011)
Zinc (Zn) and cadmium (Cd) hyperaccumulation may have evolved twice in the Brassicaceae, in Arabidopsis halleri and in the Noccaea genus. Tandem gene duplication and deregulated expression of the Zn transporter, HMA4, has previously been linked to Zn/Cd hyperaccumulation in A. halleri. Here, we tested the hypothesis that tandem duplication and deregulation of HMA4 expression also occurs in Noccaea.A Noccaea caerulescens genomic library was generated, containing 36,864 fosmid pCC1FOS™ clones with insert sizes ∼20-40 kbp, and screened with a PCR-generated HMA4 genomic probe. Gene copy number within the genome was estimated through DNA fingerprinting and pooled fosmid pyrosequencing. Gene copy numbers within individual clones was determined by PCR analyses with novel locus specific primers. Entire fosmids were then sequenced individually and reads equivalent to 20-fold coverage were assembled to generate complete whole contigs.Four tandem HMA4 repeats were identified in a contiguous sequence of 101,480 bp based on sequence overlap identities. These were flanked by regions syntenous with up and downstream regions of AtHMA4 in Arabidopsis thaliana. Promoter-reporter β-glucuronidase (GUS) fusion analysis of a NcHMA4 in A. thaliana revealed deregulated expression in roots and shoots, analogous to AhHMA4 promoters, but distinct from AtHMA4 expression which localised to the root vascular tissue.This remarkable consistency in tandem duplication and deregulated expression of metal transport genes between N. caerulescens and A. halleri, which last shared a common ancestor >40 mya, provides intriguing evidence that parallel evolutionary pathways may underlie Zn/Cd hyperaccumulation in Brassicaceae.